2022
DOI: 10.1186/s12889-022-14667-8
|View full text |Cite
|
Sign up to set email alerts
|

Is equity considered in systematic reviews of interventions for mitigating social isolation and loneliness in older adults?

Abstract: Background Social isolation and loneliness affect one in four older adults in many regions around the world. Social isolation and loneliness are shown to be associated with declines in physical and mental health. Intersecting social determinants of health influence both the risk of being socially isolated and lonely as well as the access and uptake of interventions. Our objective is to evaluate what evidence is available within systematic reviews on how to mitigate inequities in access to and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings align with previous research indicating higher levels of loneliness among those who are more deprived (Madani et al, 2022) and those who perceive themselves as being less well-off when compared with others (Ayalon, 2019). Our analysis also demonstrated that food security persists as an issue among older Indians who work, with proportions of those reporting food insecurity comparable to those in all over-60s (Muhammad et al, 2022b).…”
Section: Discussionsupporting
confidence: 91%
“…Financial insecurity in later life, including post-retirement, has been associated with greater feelings of loneliness (Cruwys et al, 2019; Loibl et al, 2022). There is strong evidence to indicate a marked socioeconomic gradient in loneliness with levels of loneliness higher among those who are more disadvantaged (Madani et al, 2022). One such indicator of disadvantage may be food security.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantially less research on loneliness and isolation among certain racial/ethnic groups, immigrant communities, diverse gender identities and sexual orientations, disability and neurodivergent population, populations with severe mental illness, people living in poverty, and other social/cultural groups. This is important given those at the greatest social disadvantage and marginalization may have the highest rates of loneliness and social isolation, and may also have heightened risk for becoming lonely and/or isolated [ 15 ].…”
Section: Main Textmentioning
confidence: 99%
“…Despite increasing attention given to social isolation in contemporary research, there is still a signi cant gap in the understanding of this phenomenon among IDPs, who are among the most socially vulnerable groups [11,12]. Therefore, this study aims to address this gap by focusing on the experiences of Ukrainian IDPs during wartime.…”
Section: Introductionmentioning
confidence: 99%